Reaktualisasi Perencanaan Partisipatif Bidang Sosial Keagamaan - Ruhiyat Ruhiyat (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2015)
State issues vis a vis Religion has long been that since the age-old debate in Europe so that the effect on religious activity and religious behavior in a region or country. Accumulation of discourse is then crystallized in the discourse of civil society and European schools of Islamic schools. Islamic civilization can open a new bridge that articulate civil societies in the new format the results of elaboration of ideas of human and religious doctrines. In the broader scope of the universality of Islam can touch every civilization of the peoples of the world, including Indonesia. At the same time, issues of poverty and ignorance the people have not been exhausted discussed. Apparently will always come to the surface without any solution. Therefore, this phenomenon into the background the need for renewal of participatory planning among the community itself. Doctrinally Muslims understand that God does not change the fate of a people, so the people that change their own destiny.